A Cdc42/RhoA regulatory circuit downstream of glycoprotein Ib guides transendothelial platelet biogenesis - Duetting, Sebastian; Gaits-Iacovoni, Frederique; Stegner, David; Popp, Michael; Antkowiak, Adrien; Van Eeuwijk, Judith M. M.; Nurden, Paquita; Stritt, Simon; Heib, Tobias; Aurbach, Katja; Angay, Oguzhan; Cherpokova, Deya; et al. (Nature Communications, 2017)
Blood platelets are produced by large bone marrow (BM) precursor cells, megakaryocytes (MKs), which extend cytoplasmic protrusions (proplatelets) into BM sinusoids. The molecular cues that control MK polarization towards sinusoids and limit transendothelial crossing to proplatelets remain unknown. Here, we show that the small GTPases Cdc42 and RhoA act as a regulatory circuit downstream of the MK-specific mechanoreceptor GPIb to coordinate polarized transendothelial platelet biogenesis. Functional deficiency of either GPIb or Cdc42 impairs transendothelial proplatelet formation. In the absence of RhoA, increased Cdc42 activity and MK hyperpolarization triggers GPIb-dependent transmigration of entire MKs into BM sinusoids. These findings position Cdc42 (go-signal) and RhoA (stop-signal) at the centre of a molecular checkpoint downstream of GPIb that controls transendothelial platelet biogenesis. Our results may open new avenues for the treatment of platelet production disorders and help to explain the thrombocytopenia in patients with Bernard-Soulier syndrome, a bleeding disorder caused by defects in GPIb-IX-V.
CRIS-Team Scopus Importer:2023-03-23